Pengaruh Modal Terhadap Pendapatan Usaha Pedagang Rempah-Rempah di Pasar Sentral Gorontalo - Mamu, Nurfirly Oliviana; Hafid, Radia; Mahmud, Melizubaida; Panigoro, Meyko; Bahsoan, Agil (Journal of Economic and Business Education, 2025)
Nurfirly Oliviana Mamu. Student Number ID 911418074. 2025. "INFLUENCE OF CAPITAL ON THE INCOME OF SPICE TRADERS AT PASAR SENTRAL (CENTRAL MARKET) GORONTALO” Undergraduate Thesis Study Program of Economics Education, Department of Economics Education, Faculty of Economics, Universitas Negeri Gorontalo. The Principal Supervisor is Dr. Radia Hafid, S.Pd., MSi. and the Co-supervisor is Dr. Melizubaida Mahmud, s.Pd., M.Si.The purpose of this study is to determine the extent to which capital influences the income of spice traders at Pasar Sentra! Gorontalo. This research used a quantitative approach, with customers as the research subjects and spice traders at Pasar Sentra) Gorontalo as the research objects. The population in this study consisted of 45 respondents, and the sample size was also 45 respondents. Data collection methods included observation, questionnaires, and interviews. Meanwhile, data analysis activities involved grouping data based on variables and respondents, presenting the data for each variable studied, and conducting calculations to test the proposed hypotheses.The study findings show that there is a positive and significant influence of capital on the income of spice traders at Pasar Sentral Gorontalo. The analysis also confirms significance, as evidenced by the t-count score being greater than the t-table score. Thus, the hypothesis stating that capital has a positive influence on the income of spice traders at Pasar Sentral Gorontalo is confirmed.